Effects of Negative Pressure Soft Tissue Therapy to Ankle Plantar Flexor on Muscle Tone, Muscle Stiffness, and Balance Ability in Patients with Stroke - Kim, Kyu Ryeong; Shin, Houng Soo; Lee, Sang Bin; Hwang, Hyun Sook; Shin, Hee Joon (Journal of International Academy of Physical Therapy Research, 2018)
The purpose of the study was to investigate the immediate effects of negative pressure soft tissue therapy on muscle tone, muscle stiffness and balance in patients with stroke. In total, 20 patients with stroke and assigned to the negative pressure soft tissue therapy group (NPST, n=10) or, placebo-negative pressure soft tissue therapy group(Placebo-NPST, n=10). Both groups underwent NPST or placebo-NPST once a day during the experimental period. MyotonPRO was used to assess the parameters for muscle tone and stiffness. Biorescue was used to assess the parameters for balance. Each group showed improvements in muscle tone, muscle stiffness, and balance ability (p<.05). Especially, Muscle tone, muscle stiffness, and anterior length in the limit of stability were the significant improvement on NPST group (p<.05). The results of the study suggest that the NPST is effective in improving muscle tone, muscle stiffness, and balance ability in patients with stroke. KCI Citation Count: 0